Afiliasi Partai Aceh Ke Partai Nasional (Studi Kasus: Keikutsertaan Kader Partai Aceh Dalam Partai Nasional Pada Pemilu Legislatif DPR RI 2019) - Rahmad Saputra; Muradi Muradi; Leo Agustino (Universitas Teuku Umar, 2020)
The purpose of this study is to look at how the relationship between local parties and national parties has not been revealed publicly, analyze the objectives of Aceh Party affiliation with national parties in the 2019 legislative elections and Analyze what strategies Aceh parties play in affiliating with national parties in the 2019 legislative elections. This study uses a qualitative approach with descriptive methods. Data collection techniques to be carried out in this study consisted of semi-structured interviews, observations, and documentation studies to find out the purpose of the political affiliation of Aceh party cadres to national parties. Through this research, it was found that the Aceh Party continues to strive to consistently fight for the interests of Aceh, especially in the issue of special autonomy that has not yet been realized. Then the Aceh Party as a local party that won the General Election in Aceh since 2009 has continued to try to maintain the acquisition of seats and expand the interests of the party, especially at the national level by placing its cadres in the national party.